(untitled) (London Journal of Medical and Health Research, 2025)
Background: Iron deficiency anemia is the most frequent cause in the world and derives from the negative balance of iron, due to an inadequate contribution or absorption in the diet, as well as physiological periods such as pregnancy. Methods: Correlational descriptive research, 42 pregnant women who attended their obstetric consultation and nutritional consultation between the ages of 18 and 40 years were interviewed. The 24-hour food consumption recall and the food frequency assessment were used. A descriptive and inferential analysis was carried out with the SPSS program. Results: Iron consumption was deficient by 76.19% in the study group. 64.29% of the pregnant women did not have anemia; Only 19.05% had mild anemia, 7.14% moderate and 9.52% severe anemia. In relation to the consumption of vitamin C, it was deficient by 40.48%. Conclusions: 35.71% of the pregnant women studied presented anemia. The percentage of adequacy of vitamin C iron consumption were deficient by 76.19% and 40.48%, respectively.The main source of heme iron consumption was the liver (Rho= 0.54); of non-heme iron, broccoli (Rho = 0.600) and of vitamin C, orange (Rho = 0.42)